Nasal Polyposis: More than a Chronic Inflammatory Disorder—A Disease of Mechanical Dysfunction—The São Paulo Position - Pezato, Rogerio; Voegels, Richard Louis; Pignatari, Shirley; Gregório, Luiz Carlos; Pinto Bezerra, Thiago Freire; Gregorio, Luciano; Balsalobre, Leonardo; Tepedino, Miguel Soares; Coronel, Nathália; Pinna, Fabio de Rezende; Mendes Neto, José; Oliveira, Pedro; Macoto, Eduardo; Stefanini, Renato; Figueiredo, Claudia; Haddad, Fernanda; Pilan, Renata; Bezerra Soter, Ana; Melo, Nelson Almeida; Candido, Danilo Almeida; Amaral, Jonatas do; Santos, Rodrigo de Paula; Van Zele, Thibaut; Fujita, Reginaldo; Dreyfuss, Juliana L.; Chamon, Wallace; Alencar, Adriano Mesquita; Perez-Novo, Claudina; Stamm, Aldo Cassol (International Archives of Otorhinolaryngology, 2019)
Introduction The importance of our study lies in the fact that we have demonstrated the occurrence of mechanical dysfunction within polypoid tissues, which promotes the development of polyps in the nasal cavity.Objective To change the paradigm of nasal polyposis (NP). In this new conception, the chronic nasal inflammatory process that occurs in response to allergies, to pollution, to changes in the epithelial barrier, or to other factors is merely the trigger of the development of the disease in individuals with a genetic predisposition to an abnormal tissue remodeling process, which leads to a derangement of the mechanical properties of the nasal mucosa and, consequently, allows it to grow unchecked.Data Synthesis We propose a fundamentally new approach to intervening in the pathological process of NP, addressing biomechanical properties, fluid dynamics, and the concept of surface tension.Conclusion The incorporation of biomechanical knowledge into our understanding of NP provides a new perspective to help elucidate the physiology and the pathology of nasal polyps, and new avenues for the treatment and cure of NP.
Keywords: airway; inflammation; nasal mucosa; nasal polyps; sinusitis